Simple rabbit model for vascular stent studies - Byzov, D.V.; Чиж, М.О.; Mikhalova, I.P.; Pushkova, Ye.N.; Sandomirsky, B.P. (Minimally Invasive Therapy and Allied Technologies. 2013.Byzov D.V., Chizh M.O., Mikhalova I.P., Pushkova Ye.N., Sandomirsky B.P. Simple rabbit model for vascular stent studies. Abstract from the 25 th conf. Intern. Soc. For Medical Innovation and technology, ISMT 2013, Baden-Baden, Germany. Minimally Invasive Therapy and Allied Technologies. 2013. 22(1): 48.: 48., 2013)
Simple rabbit model for vascular stent studies
Byzov D.V., Chizh M.O., Mikhalova I.P., Pushkova Ye.N., Sandomirsky B.P. Simple rabbit model for vascular stent studies. Abstract from the 25 th conf. Intern. Soc. For Medical Innovation and technology, ISMT 2013, Baden-Baden, Germany. Minimally Invasive Therapy and Allied Technologies. 2013. 22(1): 48.
Keywords: vascular stent; rabbit model